Prevalence of Elevated Blood Pressure and Association with Obesity in Egyptian School Adolescents - Mostafa A. Abolfotouh; Sunny A. Sallam; Mohammed S. Mohammed; Amany A. Loutfy; Ali A. Hasab (International Journal of Hypertension)
Aim. To investigate the relationship between high blood pressure (HBP) and obesity in Egyptian adolescents. Methods. A cross-sectional study of 1500 adolescents (11–19 years) in Alexandria, Egypt, was conducted. Resting BP was measured and measurements were categorized using the 2004 fourth report on blood pressure screening recommendations. Additional measures included height, weight, and waist and hip circumferences. Obesity was determined based on BMI, waist circumference (WC) and waist-to-hip ratio (WHR), and waist-to-height ratio (WHtR) indicators. Crude and adjusted odds ratios were used as measures of association between BP and obesity. Results. Prevalence rates of prehypertension and hypertension were 5.7% and 4.0%, respectively. Obesity was seen in 34.6%, 16.1%, 4.5%, and 16.7% according to BMI, WHR, WC, and WHtR, respectively. Adjusting for confounders, HBP was significantly associated with overall obesity based on BMI (OR=2.18, 95%, CI=1.38-3.44) and central obesity based on WC (OR=3.14, 95%, CI=1.67-5.94). Conclusion. Both overall obesity and central obesity were significant predictors of HBP in Egyptian adolescents.